Screening for Intimate Partner Violence against Women in Healthcare Sweden: Prevalence and Determinants - Lawoko, Stephen; Sanz, Soren; Helstrom, Lotti; Castren, Maaret (International Scholarly Research Notices, 2011)
Intimate partner violence (IPV) is defined as behaviours within an intimate relationship that cause physical, sexual, or psychological harm, including acts of physical aggression, sexual coercion, psychological abuse, and controlling behaviours [1]. Though IPV is prevalent among both men and women, its impact on abused women’s health is farmore pronounced and documented, prompting call for action from reknown health researchers and organisations in a bid to break the cycle of abuse. Women experiencing IPV suffer a wide range of health complications resulting from physical, sexual, and psychological assaults manifest in severe physical injuries [2–4], reproductive health problems including terminated pregnancies, undesired pregnancies and child loss during infancy [5–7], symptoms of depression, anxiety and posttraumatic stress disorder, and risky health behaviours such as unhealthy feeding habits, substance abuse, alcoholism, and suicidal behaviours [8–10].
Keywords: Intimate Partner Violence; Women; Healthcare Sweden